Produção de lipases por microrganismos isolados de efluentes de laticínios através de fermentação submersa - Roveda, Mirela (2007)
The enzymatic production is one of the most promising fields inside of the technologies for the synthesis of compound from the high value added, being in constant growth for the great capacity of the microorganisms to carry out chemical transformations. Among the products gotten from fermentative processes through microorganisms are the enzymes. The enzymes produced from fermentative processes have been used for the ambient control for several ecosystems, being that many of these enzymes can be produced from industrial residues, reducing the costs production. The effluent of dairy is rich in slowly biodegradable fats that make difficult the treatment of these effluents in low temperatures. Lipases are a group of enzymes that catalyzes hydrolysis of long chains of triglycerides transforming them into glycerides and fatty acids. Microbial lipase has received great attention, constituting the most important group of enzymes for the biotechnological application. Lipases have being used in the reduction of the lipids concentration contained in the effluent, promoting hydrolysis of the presents oils and fats. The objective of this work was to evaluate the production of lipase from isolated fungus from the dairy effluent. The effluent was collected in the exit of the equalizer (P3) and the exit of the aerator (P6) from an effluent treatment station at a dairy industry in the region of Passo Fundo/RS being characterized as for DBO, DQO, phosphorous, nitrogen and oils and greases, in accordance with the methodology described at APHA (1995). It was carried out through the isolation of microorganisms from the collection points through techniques of series dilutions followed of the plating in medium PDA acidified and incubate at 30° C during 5 days. The isolated microorganisms had been identified through micro culture techniques. The selection of the fungi with potential of lipases production was evaluated from the growth of them in medium PDA added with olive oil as a carbon source